(untitled) (International Journal of Food and Nutritional Sciences, 2024)
Introduction: Fluoride plays a key role in prevention of dental caries and is also an essential element for oral health promotion both in children and adults. Aim: The aim of the present study was to evaluate the effect of surface coating (petroleum jelly, G-Coat Plus) on the fluoride releasing property of conventional Glass Ionomer Cement (GIC) and Zirconomer. Materials and Methods: A total of 30 disk shaped brass mold specimens (6±0.1mm in diameter and 2±0.1mm thickness) for each test group were fabricated with conventional GIC (Group A) and Zirconomer (Group B). These test groups were further divided into three subgroups of 10 each. The unprotected specimens act as control (Group A1 and B1), G-Coat Plus specimens as (Group A2 and B2) and for the remaining specimens petroleum jelly was applied (Group A3 and B3). Fluoride ion concentration was measured with a combination of fluoride ion specific electrode and ion analyzer for every 24 hours for 15 days. The data was statistically analyzed using Kruskal Wallis and Mann-Whitney U test. Results: The Group B released significantly more fluoride than Group A. Among all the subgroups the greatest amount of fluoride was released from Group B1, in the first 24 hours followed by A1 and B2. The least was observed on 15th day with Group B3 and A3.